Immunometabolic analysis of primary murine group 2 innate lymphoid cells: a robust step-by-step approach - Krisna, Sai Sakktee; Deagle, Rebecca C.; Ismailova, Nailya; Esomojumi, Ademola; Roy-Dorval, Audrey; Roth, Frederik; Berberi, Gabriel; del Rincon, Sonia V.; Fritz, Jörg H. (Frontiers in Immunology, 2025)
Group 2 Innate Lymphoid Cells (ILC2s) have recently been shown to exert key regulatory functions in both innate and adaptive immune response networks that drive the establishment and progression of type 2 immunity. Although mainly tissue resident, ILC2s and their crosstalk within tissue microenvironments influence metabolism at both the local and systemic levels. In turn, the energetic demand and metabolic status within these systems shape the diverse phenotypes and effector functions of ILC2s. Deciphering these metabolic networks in ILC2s is therefore essential in understanding their various roles in health as well as their associated pathophysiologies. Here we detail a framework of experimental approaches to study key immunometabolic states of primary murine ILC2s and link them to unique phenotypes and their corresponding functionality. Utilizing flow cytometry, Single Cell ENergetic metabolism by profilIng Translation inHibition (SCENITH), and the Seahorse platform we provide a framework that allows in-depth analysis of cellular bioenergetic states to determine the immunometabolic wiring of ILC2s. Connecting immunometabolic states and networks to ILC2 phenotypes and effector functions with this method will allow future in-depth studies to assess the potential of novel pharmaceutics in altering ILC2 functionality in clinical settings.